Safety and efficacy of the amino acid-crosslinked hyaluronic acid in the treatment of temple hollowing - Yanping Guo; Puzhen Li; Wuhan Wei; Qiang Li; Caiqi Shen; Xiaoying Zhuo; Yujie Luo; Jie Liu; Peisheng Jin; Xueyang Li (Asian Journal of Surgery)
Background: Loss of volume in the temples is an early sign of aging and often gives the impression of a gaunt and emaciated appearance. Objective: The authors conduct a clinical study to investigate the safety and effectiveness of the amino acid crosslinked hyaluronic acid (ACHA) for the treatment of temple hollowing. Methods: 75 subjects with Temple Hollowing Scale (THS) from 2 to 4 were enrolled and assigned according to the ratio of 2 (ACHA group, n = 50): 1 (no treatment control group, n = 25). All subjects were assessed at the 12-month follow-up visit using the THS, Global Aesthetic Improvement Scale (GAIS), ultrasound, and three-dimensional scanning. Subjects were instructed to report any adverse events (AEs) within 14 days after the ACHA treatment. Results: An average volume of 4.72 ± 1.13 ml was injected into the temples. We received 18 treatment-related AEs reported by 10 subjects. Compared with the control group, THS, GAIS, and soft tissue thickness were significantly improved in the ACHA group at 1 month, 6, and 12 months after injection. Three-dimensional scanning showed that ACHA could maintain a certain volume in the temple 12 months after ACHA injection. Conclusions: ACHA is an effective and safe hyaluronic acid for patients with minimal to severe temple hollowing.